2006
DOI: 10.3846/1648715x.2006.9637545
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Procurement Trends and Partnership Management in Fm Services ‐ a Finnish Survey

Abstract: The aim of this paper is to review procurement trends of facilities management (FM) services and to describe the partnership control mechanisms that contribute to the success of FM partnerships. The investigation is based on a questionnaire survey, which was carried out in Finland. It was found that a transition ‐ similar to those in other industries ‐ towards closer relationships and bigger purchase entities is taking place also in the FM context. In most cases, the choice of the partnering approach is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…This is consistent with a host of supply management Note: X1 = analytical, X2 = understanding general business conditions, X3 = planning, X4 = strategic thinking, X5 = structuring supplier relationships, X6 = managing the supply base, and X7 = project management. literature (e.g., Eltantawy, 2008;Lehtonen & Salonen, 2006). Structuring supplier relationships, however, is relatively less important in determining both status and integration.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 97%
“…This is consistent with a host of supply management Note: X1 = analytical, X2 = understanding general business conditions, X3 = planning, X4 = strategic thinking, X5 = structuring supplier relationships, X6 = managing the supply base, and X7 = project management. literature (e.g., Eltantawy, 2008;Lehtonen & Salonen, 2006). Structuring supplier relationships, however, is relatively less important in determining both status and integration.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 97%
“…As noted by Schotanus & Telgen (2007, p. 53): "the concept of cooperative purchasing seems to be especially interesting for public organisations, for instance, for organisations like public hospitals, schools, ministries, or municipalities." This approach has also been used in the private sector over the last decade (Becky, 2013;Lehtonen & Salonen, 2006).…”
Section: Definition Of Purchasing Groupsmentioning
confidence: 99%
“…Theoretically elaborated studies of FM relationships have been carried out by Finnish researchers, who have analysed these contracts in relation to the literature on buyer-seller relationships in other industries. There has been a trend for Finnish companies to abandon transactional relations in favour of wider service packages and partnering approaches, and Lehtonen and Salonen (2006) found that relationships in FM formally had many characteristics in common with both traditional arms' length relationships and with partnerships. For e xample, a lthough there were learning and development objectives, choice of partner was generally based on price and there was no sharing of benefits and risks.…”
Section: Research On Fm Contracts and Relationshipsmentioning
confidence: 99%
“…A change of FM partner will thus not influence business strategy, and FM partnerships are seen as intrinsically more operational than strategic (Lehtonen and Salonen, 2006). However, many relationships are close with high levels of trust and commitment, and Lehtonen and Salonen (2006) argue that this is because services are delivered on the premises of clients. They also found that operational level contacts were considered important, as well as the relations between front line staff and end-users.…”
Section: Research On Fm Contracts and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation